2011
DOI: 10.1002/jez.b.21395
|View full text |Cite
|
Sign up to set email alerts
|

Modular phenotypic plasticity: divergent responses of barnacle penis and feeding leg form to variation in density and wave-exposure

Abstract: Traits can evolve both in response to direct selection and in response to indirect selection on other linked traits. Although the evolutionary significance of coupled traits (e.g., through shared components of developmental pathways, or through competition for shared developmental resources) is now well accepted, we know comparatively little about how developmental coupling may restrict the independent responses of two or more phenotypically plastic traits in response to conflicting environmental cues. Such st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(64 reference statements)
1
9
1
Order By: Relevance
“…Although previous work in insects showed that development of genitalia are canalized and show little evidence of plasticity (House and Simmons 2007), experiments in barnacles showed that genitalia can respond in a phenotypically plastic manner to wave action (Neufeld and Palmer 2008), and social environment, in which individuals grow shorter penises when colonies are more dense (Hoch 2009;Neufeld 2011). Similarly, we have found that some species of ducks have phenotypically plastic male genitalia in at least some species in response to their social environment (PLR Brennan, K Zyscowski, and RO Prum, unpubl.…”
Section: Distinguishing Between Mechanisms Of Genital Coevolutionmentioning
confidence: 99%
“…Although previous work in insects showed that development of genitalia are canalized and show little evidence of plasticity (House and Simmons 2007), experiments in barnacles showed that genitalia can respond in a phenotypically plastic manner to wave action (Neufeld and Palmer 2008), and social environment, in which individuals grow shorter penises when colonies are more dense (Hoch 2009;Neufeld 2011). Similarly, we have found that some species of ducks have phenotypically plastic male genitalia in at least some species in response to their social environment (PLR Brennan, K Zyscowski, and RO Prum, unpubl.…”
Section: Distinguishing Between Mechanisms Of Genital Coevolutionmentioning
confidence: 99%
“…With few neighbors, barnacles have shorter feeding legs (Lopez et al. ; Neufeld ) and longer penises (Neufeld ). In this situation, shorter feeding legs may help barnacles cope with the reduced boundary layer, and longer penises may help them reach more distant neighbors.…”
mentioning
confidence: 99%
“…; Marchinko ; Marchinko & Palmer ; Chan & Hung ; López et al. , , ; Hoch , , ; Neufeld ; Neufeld & Palmer ; Neufeld & Rankine ; Table ). However, we did note variation in cirrus and penis morphology with respect to tidal height.…”
Section: Discussionmentioning
confidence: 97%
“…; Marchinko ; Marchinko & Palmer ; Chan & Hung ; López et al. , , ; Hoch ; Neufeld ; Neufeld & Rankine ), which show dramatic morphological differences between environments and which had a large proportion of the variance in morphology explained by environmental variables (Table ). The barnacles from this study may lack such strong responses because they use a different feeding strategy and thus respond to the risks of crashing waves differently.…”
Section: Discussionmentioning
confidence: 99%